Business Opportunity of AEK COPY / Mohammad Fathul Azim Faisal Abdul Aziz Faisal - Abdul Aziz Faisal, Mohammad Fathul Azim Faisal (2022)
Due to the pandemic season, which had a tremendous impact on our society, many vendors did not dare to take any more risks to maintain their business, and many businesspersons were believed to have gone bankrupt during the pandemic. Modest traders are also impacted because they can only make a small profit and must sell items at a low cost. After the third season of PKP concluded, the Prime Minister announced that the business may be restarted, so I began looking for things to sell to earn money and purchase my own necessities. So, I decided to sell a cup of AEK COPY for RM4.00. In recent years, coffee drinks have grown in popularity and trending among young people. Furthermore, my estimates show that the teen population in my neighbourhood is higher than the adult population. After that, a new trending from young people may can increasing demand of coffee. As a result, I am optimistic that my company will run smoothly and according to my plan. Business operations will be opened at home.